Analysis of Taxpayer Compliance with Motor Vehicle Tax Revenue in Ponorogo Regency - Rosiana Eka Pratiwi; Denty Arista (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2025)
This research aims to analyze the level of taxpayer compliance with the Motor Vehicle Tax in Ponorogo Regency. Taxes play a crucial role in national development and serve as a major source of state revenue. Despite the increase in the number of taxpayers and the realization of PKB revenue from 2020 to 2024, taxpayer compliance remains suboptimal, with arrears continuing to rise. This study employed a descriptive qualitative method, utilizing questionnaires distributed to 105 taxpayers in Ponorogo Regency. The findings indicate that taxpayers in Ponorogo Regency have a strong understanding of, awareness of, and compliance with their tax obligations. However, there are several obstacles that contribute to delays in tax payments, such as negligence, unregistered motor vehicles, and economic factors. Recommendations to enhance taxpayer compliance include more comprehensive outreach and implementation of a Motor Vehicle Tax incentive program to alleviate late fees. The research novelty lies in the testing of Stanley Milgram's compliance theory against the implementation of the latest regional tax regulations enacted during the current research year, specifically East Java Governor Regulation Number 34 of 2024 concerning the Implementing Guidelines for Regional Tax Collection.